New approach to design solid block copolymer electrolytes for 40 °C lithium metal battery operation. (1st June 2017) - Lassagne, A.; Beaudoin, E.; Ferrand, A.; Phan, T.N.T.; Davidson, P.; Iojoiu, C.; Bouchet, R.
Abstract: Block copolymer electrolytes (BCEs) are promising solid electrolytes in lithium metal batteries thanks to the versatility of the block chemistry. In this work, several triblock BCEs, based on a modified poly(ethylene oxide) (PEO) central block and two polystyrene (PS) lateral blocks, have been synthetized by controlled radical polymerization. By including few chemical defects homogeneously distributed along the PEO chains, we managed to break its stereo-regularity, which allows lowering significantly its melting temperature, and therefore obtaining good ionic conductivity at 40 °C. The mechanical properties were controlled by the length of the peripheral polystyrene blocks, which were varied from 2.9 to 11.3 kg/mol. We performed systematic analysis of morphologies, thermodynamic properties, mechanical properties, and ionic transport properties of these new BCEs that we compared to a triblock copolymer electrolyte based on a PEO central block. Finally, we characterized the performances of the BCE with the best compromise between mechanical strength and conductivity as electrolyte in a lithium metal battery using LiFePO4 as positive electrode active material. This device has been cycled at different rates from 40 °C to 80 °C with promising performances especially at 40 °C.